Fatigue as a predictor of sickness absence: results from the Maastricht cohort study on fatigue at work. (1st June 2003) - Janssen, N; Kant, IJ; Swaen, G M H; Janssen, P P M; Schröer, C A P
Abstract : Objectives: To investigate whether there is a relationship between fatigue and sickness absence. Two additional hypotheses were based on the theoretical distinction between involuntary, health related absence and voluntary, attitudinal absence. In the literature, the former term is usually used to describe long term sickness absence, the latter relates to short term sickness absence. In line with this, the first additional hypothesis was that higher fatigue would correspond with a higher risk of long term, primarily health related absence. The second additional hypothesis was that higher fatigue would correspond with a higher risk of short term, primarily motivational absence. Methods: A multidimensional fatigue measure, as well as potential sociodemographic and work related confounders were assessed in the baseline questionnaire of the Maastricht cohort study on fatigue at work. Sickness absence was objectively assessed on the basis of organisational absence records and measured over the six months immediately following the baseline questionnaire. In the first, general hypothesis the effect of fatigue on time-to-onset of first sickness absence spell during follow up was investigated. For this purpose, a survival analysis was performed. The effect of fatigue on long term sickness absence was tested by a logistic regression analysis. The effect of fatigue on short term sickness absence was investigated by performing a survival analysis with time-to-onset of first short absence spell as an outcome. Results: It was found that higher fatigue decreased the time-to-onset of the first sickness absence spell. Additional analyses showed that fatigue was related to long term as well as to short term sickness absence. The effect of fatigue on the first mentioned outcome was stronger than the effect on the latter outcome. Potential confounders only weakened the effect of fatigue on long term absence. Conclusions: Fatigue was associated with short term but particularly with long term sickness absence. The relation between fatigue and future sickness absence holds when controlling for work related and sociodemographic confounders. Fatigue as measured with the Checklist Individual Strength can be used as a screening instrument to assess the likelihood of sickness absence in the short term.